Superdog : the heart of a hero - Buehner, Caralyn; Buehner, Mark ([New York] : HarperCollins, 2004)
Tired of being overlooked because he is so small, a big-hearted dog named Dexter transforms himself into a superhero.
Wilson's Children.
School Library Journal starred.
Book Links (A.L.A.).
3.0
K-3
Keywords: Dogs -- Fiction; Heroes -- Fiction; Size -- Fiction; Dogs -- Fiction; Heroes and heroines -- Fiction; Size -- Fiction; Dogs -- Fiction; Heroes -- Fiction